2018
DOI: 10.1016/j.jbspin.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

2018 update of French recommendations on the management of postmenopausal osteoporosis

Abstract: The updated recommendations place strong emphasis on the treatment of women with severe fractures, in whom the use of osteoporosis medications is recommended. All the available osteoporosis medications are suitable in patients with severe fractures; zoledronic acid deserves preference as the fist-line drug after a hip fracture. In patients with or without non-severe fractures, the decision to use osteoporosis medications is based on bone mineral density values and in challenging cases, on probabilities supplie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
61
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(74 citation statements)
references
References 111 publications
1
61
0
12
Order By: Relevance
“…Percentages based on number of patients enrolled who are at increased risk of fragility fracture using the base definition Our data demonstrate that oral bisphosphonates are still the most widely used agents, comprising 58% of first-line OP medication (58.3%) compared with 28% receiving denosumab, and only 8% accessing parenteral bisphosphonate therapy. The vast majority of patients on second-line therapy received non-oral treatment (denosumab, 76%; parenteral BP, 10%), a pattern that is consistent with recommendations in key European guidelines [9,[14][15][16].…”
Section: Discussionsupporting
confidence: 54%
“…Percentages based on number of patients enrolled who are at increased risk of fragility fracture using the base definition Our data demonstrate that oral bisphosphonates are still the most widely used agents, comprising 58% of first-line OP medication (58.3%) compared with 28% receiving denosumab, and only 8% accessing parenteral bisphosphonate therapy. The vast majority of patients on second-line therapy received non-oral treatment (denosumab, 76%; parenteral BP, 10%), a pattern that is consistent with recommendations in key European guidelines [9,[14][15][16].…”
Section: Discussionsupporting
confidence: 54%
“…Osteoporosis is preventable and treatable using the various pharmacological therapies available and this management reduces fracture rates [7,8]. Dual-Energy X-ray Absorptiometry (DEXA) scan is the cornerstone of osteoporosis screening, while the Fracture Risk Assessment Tool (FRAX) score adds valuable further information when evaluating fracture risk [9,10]. Despite the clear links between osteoporosis and fracture, screening rates are low in primary care with only 21.1, 26.5 and 12.8% of women aged 50-64, 65-79 and > 80 years, respectively, being screened in a large US study [5], while only 10.8% of women > 65 years underwent osteoporosis screening in a US primary care setting [11].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis has been identified as a major public health concern due to the serious consequences of osteoporotic fractures and its increasing prevalence with population ageing [2][3][4] . The main objective of anti-osteoporotic treatment is to reduce the risk of fracture 5,6 . Bisphosphonates are antiresorptive medications which have demonstrated their efficacy to prevent osteoporotic fracture [7][8][9][10] .…”
mentioning
confidence: 99%
“…Bisphosphonates are antiresorptive medications which have demonstrated their efficacy to prevent osteoporotic fracture [7][8][9][10] . Oral bisphosphonates are recommended among the first-line treatments for osteoporosis 5,6 . Several studies have indicated that non-persistence and poor implementation were associated with increased risk of fracture 11,12 and reduced drug effectiveness, which consequently results in significant higher clinical burden and healthcare costs 13 .…”
mentioning
confidence: 99%
See 1 more Smart Citation